The Influence of Perceived Trust, Usefulness, Risks and Financial Knowledge on Interest in Using SPayLater - Salsabila, Shafa Tasya; Dewi, Yuli Kartika; Bachtiar, Sonia (Jurnal Manajemen Bisnis, 2024)
This study aims to determine the effect of perceived trust, usefulness, risk, and financial knowledge on interest in using SpayLater. This research method uses a quantitative approach with a research sample of 231 generation Z communities in Java. The data collected was tested using the SEM-PLS technique through SmartPLS 4.0 software. The test results show that perceived trust, benefits, and risks have a positive and significant effect on interest in using SpayLater. Meanwhile, financial knowledge does not affect interest in using SpayLater. These results are expected to provide positive implications for generation Z, who should be more careful when choosing to transact using the PayLater facility.